2014
DOI: 10.1590/s1517-83822014000300041
|View full text |Cite
|
Sign up to set email alerts
|

Impairments of mecA gene detection in bovine Staphylococcus spp.

Abstract: Staphylococcus aureus antimicrobial resistance, especially to beta-lactams, favors treatment failures and its persistence in herd environment. This work aimed to develop a more specific primer for mecA gene detection based on the comparison of the conserved regions from distinct host origins and also investigated the presence of homologue mecALGA251 in bovine strains. A total of 43 Staphylococcus spp. were included in this study, comprising 38 bovine S. aureus, two human and three equine coagulase-negative sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 26 publications
1
19
0
3
Order By: Relevance
“…They were identified as S. chromogenes (3), S. epidermidis (3), S. hominis (2) and S. hyicus (1), but only 2 S. epidermidis were positive for the mecA and mecRI genes. Another 9 isolates, 6 S. sciuri and 3 S. chromogenes, were also positive for the mecA gene (Murakami et al, 1991) and other 6 S. sciuri were positives for the mecA variant (Melo et al, 2014), but they were susceptible to all antimicrobials. They were also negative for the mecI and mecRI genes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They were identified as S. chromogenes (3), S. epidermidis (3), S. hominis (2) and S. hyicus (1), but only 2 S. epidermidis were positive for the mecA and mecRI genes. Another 9 isolates, 6 S. sciuri and 3 S. chromogenes, were also positive for the mecA gene (Murakami et al, 1991) and other 6 S. sciuri were positives for the mecA variant (Melo et al, 2014), but they were susceptible to all antimicrobials. They were also negative for the mecI and mecRI genes.…”
Section: Resultsmentioning
confidence: 99%
“…Even though the mecA gene was found in 11 strains, only two of them showed resistance to cefoxitin. The mecA variant typical from bovine samples, impossible to detected by routine PCR (Melo et al, 2014), was found in 6 S. sciuri, that were all susceptible to cefoxitin too. Kim et al (2013) made a study explaining the hetero-resistance to the betalactam family of antibiotics in methicillin resistant isolates.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Detection of the mecA gene in isolates of bovine origin with oxacillin resistance phenotype is problematic. Melo et al (2014) detected point mutations in the annealing region of primer, which resulted in design of new primers for the detection of mec gene in isolated bovine (mec bovine). GarciaAlvarez et al (2011) also detected mutations in the gene mec, and described a new allele called mecC, this gene has been found in humans and animals, but until the present date, this allele was not detected in the Americas.…”
Section: Discussionmentioning
confidence: 99%
“…After overnight incubation at 35 °C, followed by inhibition zone measurement,16, 17 the results were evaluated as per the interpretation criteria following the CLSI standards 15 . PCR was performed for mec A using primers designed by Murakami et al 24 and Melo et al 25 and for bla Z according to Rosato et al 26 (Table 1). …”
Section: Methodsmentioning
confidence: 99%